2022
DOI: 10.1073/pnas.2115854119
|View full text |Cite
|
Sign up to set email alerts
|

Conformation and dynamic interactions of the multipartite genome in Agrobacterium tumefaciens

Abstract: Bacterial species from diverse phyla contain multiple replicons, yet how these multipartite genomes are organized and segregated during the cell cycle remains poorly understood. Agrobacterium tumefaciens has a 2.8-Mb circular chromosome (Ch1), a 2.1-Mb linear chromosome (Ch2), and two large plasmids (pAt and pTi). We used this alpha proteobacterium as a model to investigate the global organization and temporal segregation of a multipartite genome. Using chromosome conformation capture assays, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(69 citation statements)
references
References 68 publications
4
61
0
Order By: Relevance
“…To test how the centromeric proteins contribute to the replication and segregation of the replicons, we visualized the replication origins in the absence of ParB1 or RepB Ch2 . To label the origins in live cells, we inserted a visualization cassette, mcherry-parB P1 -parS P1 , at a position 50 kb away from ori1 , or ygfp-parB pMT1 -parS pMT1 , 57 kb away from ori2 or 11 kb away from oAt ( 11 , 27 ). Each cassette contains yGFP or mCherry fused to ParB from the pMT1 or P1 plasmid and the parS site of pMT1 or P1, respectively ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To test how the centromeric proteins contribute to the replication and segregation of the replicons, we visualized the replication origins in the absence of ParB1 or RepB Ch2 . To label the origins in live cells, we inserted a visualization cassette, mcherry-parB P1 -parS P1 , at a position 50 kb away from ori1 , or ygfp-parB pMT1 -parS pMT1 , 57 kb away from ori2 or 11 kb away from oAt ( 11 , 27 ). Each cassette contains yGFP or mCherry fused to ParB from the pMT1 or P1 plasmid and the parS site of pMT1 or P1, respectively ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Like many other species, the primary chromosome (Ch1) replicates first, followed by the replication of secondary replicons (Ch2 and plasmids) ( 5 10 ). Our recent study ( 11 ) characterized the organization of this multipartite genome and revealed that the origins of the four replicons are clustered together and localized at the two cell poles ( Fig. 1A ).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations